2021
DOI: 10.1088/2058-8585/ac428e
|View full text |Cite
|
Sign up to set email alerts
|

Particle dynamics in drying colloidal solution using discrete particle method

Abstract: We study particle dynamics in drying colloidal solutions using the numerical simulation with discrete particle method (DPM). Simulations of two different systems were conducted; the drying dynamics of monodispersed and binary mixture of colloidal solution, and compared with those from the previous studies. In the monodispersed colloidal solution, the time evolution of particle concentration profile for varying Péclet number was simulated with the same initial particle concentration. In the binary colloidal sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(101 reference statements)
0
1
0
1
Order By: Relevance
“…Therefore, it is important to understand the dynamics of dispersed particles in an evaporating sessile droplet, to control the desired morphology. Many studies have demonstrated that the final pattern is influenced by the evaporation mechanism [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], flow dynamics inside the droplet [ 37 , 38 , 39 , 40 ] and multi-body interactions [ 41 , 42 , 43 , 44 , 45 , 46 ]. It was observed that a variety of patterns can be formed by controlling these effects, showing spider-web [ 47 , 48 ], multi-ring [ 49 , 50 , 51 ] and spot-like [ 52 , 53 ] deposits as well as homogeneous morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to understand the dynamics of dispersed particles in an evaporating sessile droplet, to control the desired morphology. Many studies have demonstrated that the final pattern is influenced by the evaporation mechanism [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], flow dynamics inside the droplet [ 37 , 38 , 39 , 40 ] and multi-body interactions [ 41 , 42 , 43 , 44 , 45 , 46 ]. It was observed that a variety of patterns can be formed by controlling these effects, showing spider-web [ 47 , 48 ], multi-ring [ 49 , 50 , 51 ] and spot-like [ 52 , 53 ] deposits as well as homogeneous morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Для улучшения этих моделей, алгоритмов и программ необходимо разрабатывать дополнительные модули, позволяющие учесть различные эффекты, влияющие на формирование осадков, в том числе и гидродинамику. В коммерческом пакете Comsol Multiphysics есть модули, позволяющие рассчитывать динамику частиц и гидродинамику [46], но цена на этот пакет относительно высокая. Это касается и дополнительных тулбоксов к Matlab [47].…”
unclassified